The perilous life of symphony orchestras : artistic triumphs and economic challenges - Flanagan, Robert J. (Yale University Press, 2012)
"This book analyzes the economic challenges facing U.S. symphony orchestras and contrasts the experience of orchestras in the United States (where there is little direct government support) and abroad (where governments typically provide large direct subsidies). Robert J. Flanagan explains the tension between artistic excellence and financial jeopardy that confronts most symphony orchestras and analyzes proposed solutions. The economic difficulties are rooted in the limited opportunities for increasing productivity in the arts, a situation that produces ongoing cost pressures and structural budget deficits."--Jacket